BUTTERFLY HUG SEBAGAI INTERVENSI NONFARMAKOLOGIS UNTUK MENGATASI ANXIETY PADA PASIEN CKD - Lia Nur Aisah; Dewi Suryandari (Literasi Intelektual, 2025)
Background: Chronic Kidney Disease (CKD) is a condition in which kidney function gradually declines due to kidney damage. CKD occurs when the kidneys are unable to eliminate metabolic waste from the body or perform their regular functions. Patients with CKD generally undergo hemodialysis, and those undergoing hemodialysis often experience anxiety. One of the non-pharmacological interventions for managing anxiety is the Butterfly Hug technique. Objective: This study aimed to examine the effect of the Butterfly Hug on anxiety levels in CKD patients undergoing hemodialysis. Method: The research method employed was a quasi-experimental design with a pre- and post-test without a control group. The study population consisted of 66 patients undergoing hemodialysis at UNS Hospital Surakarta. The sampling technique used was consecutive sampling, with a total of 40 respondents selected according to the inclusion and exclusion criteria of the hemodialysis unit at UNS Hospital Surakarta. Data were analyzed using the Wilcoxon test. Data collection was carried out using the DASS-42 questionnaire to assess anxiety levels. Subsequently, the Butterfly Hug intervention was administered in accordance with the standard operating procedure (SOP) for the technique. The Butterfly Hug was implemented twice per week, with each session lasting 10 minutes. Result: The results of the study showed that, in the pre-test, 60.0% of respondents experienced mild anxiety, whereas in the post-test, 80.0% of respondents reported normal anxiety levels. Conclusion: The p-value obtained was 0.000 (<0.05), indicating that the Butterfly Hug intervention had a significant effect on reducing anxiety levels in CKD patients undergoing hemodialysis at UNS Hospital Surakarta.